2011
DOI: 10.1155/2011/165837
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vessel Development and Expansion in Ewing's Sarcoma: A Review of the Vasculogenesis Process and Clinical Trials with Vascular-Targeting Agents

Abstract: Ewing's sarcoma accounts for a disproportionately high portion of the overall pediatric mortality rate compared to its rare incidence in the pediatric population. Little progress has been made since the introduction of traditional chemotherapies, and understanding the biology of the tumor is critical for developing new therapies. Ewing's sarcomas rely on a functional vascular supply, which is formed by a combination of angiogenesis and vasculogenesis. Recent insights into the molecular regulation of bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The cure rates for Ewing’s sarcoma patients, especially those who present with metastasis, have remained unchanged for over 20 years, emphasizing the urgency for new therapies (30). We previously demonstrated that vasculogenesis is essential for the expansion of Ewing’s sarcoma tumor vasculature and that inhibiting this process, inhibits tumor growth (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…The cure rates for Ewing’s sarcoma patients, especially those who present with metastasis, have remained unchanged for over 20 years, emphasizing the urgency for new therapies (30). We previously demonstrated that vasculogenesis is essential for the expansion of Ewing’s sarcoma tumor vasculature and that inhibiting this process, inhibits tumor growth (12, 13).…”
Section: Discussionmentioning
confidence: 99%
“…EWS basically rely on a combination of angiogenesis and vasculogenesis [20]. Apart from what is known about the role of vasculogenesis in EWS vascular tumor blood supply [20], little is known about the regulation of angiogenesis sprouting. As shown previously, CAV1 silencing in EWS cells impairs tumor growth in nude mice [2].…”
Section: Discussionmentioning
confidence: 99%
“…EWS cells express a variety of pro-angiogenic factors [14], [20], [26]. Analysis of the levels of a group of pro-angiogenic factors released by tumor cells showed that only the expression of the bFGF gene was reduced by CAV1 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…One new treatment option focuses on anti-angiogenic therapy, based on the observation that EWS-ETS fusion proteins upregulate the transcription of vascular endothelial growth factor (VEGF), which is overexpressed in Ewing tumors and whose inhibition can suppress growth of Ewing tumor cells in vitro [8688]. Respective clinical trials are still ongoing and their outcomes are eagerly awaited [89]. …”
Section: Chromosomal Translocations In Ewing Tumorsmentioning
confidence: 99%